A mutation in reverse transcriptase of bis(heteroaryl)piperazine-resistant human immunodeficiency virus type 1 that confers increased sensitivity to other nonnucleoside inhibitors. - Dueweke, T J (1993)
Several nonnucleoside inhibitors of human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) have been described, including Nevirapine, thiobenzimidazolone (TIBO) derivatives, pyridinone derivatives such as L-697,661, and the bis(heteroaryl)piperazines (BHAPs). HIV-1 resistant to L-697,661 or Nevirapine emerges rapidly in infected patients treated with these drugs, and the resistance is caused primarily by substitutions at amino acids 181 and 103 of RT that also confer cross resistance to the other nonnucleoside inhibitors. We describe derivation and characterization of two BHAP-resistant HIV-1 variants that differ from this pattern of cross resistance. With both variants, HIV-1 resistance to BHAP RT inhibitors was caused by a RT mutation that results in a proline-to-leucine substitution at amino acid 236 (P236L). Rather than conferring cross resistance to other RT inhibitors, this substitution sensitized RT 7- to 10-fold to Nevirapine, TIBO R82913, and L-697,661 without influencing sensitivity to nucleoside analogue RT inhibitors. This sensitization caused by P236L was also observed in cell culture with BHAP-resistant HIV-1. The effects of the P236L RT substitution suggest that emergence of BHAP-resistant virus in vivo could produce a viral population sensitized to inhibition by these other nonnucleoside RT inhibitors.